2009
DOI: 10.1089/fpd.2008.0244
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Static Magnetic Field on Cell Growth, Viability, and Differential Gene Expression in Salmonella

Abstract: In the present study, we investigated the effect of exposure to A static magnetic field (SMF) on cell growth, viability, and gene expression of Salmonella enterica subsp. enterica serovar Hadar. Our results indicated that SMF exposure (200 mT, 13 hours) failed to alter cellular growth but induced a decrease of colony-forming units (CFU) between 3 and 6 hours followed by an increase from 6 to 9 hours. The analysis of the differential expression of rpoA, dnaK, katN, and 16S rRNA genes under SMF exposure (200 mT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Many studies have shown that low-density static and low frequency magnetic field inhibited the growth of Escherichia coli (Filipic, Kraigher, Tepus, Kokol, & Mandic-Mulec, 2012;Fojt, Strasak, Vetterl, & Smarda, 2004). El May et al (2009) has proved that static magnetic field (SMF) exposure could alter cell growth, viability, and gene expression in some bacteria.…”
mentioning
confidence: 99%
“…Many studies have shown that low-density static and low frequency magnetic field inhibited the growth of Escherichia coli (Filipic, Kraigher, Tepus, Kokol, & Mandic-Mulec, 2012;Fojt, Strasak, Vetterl, & Smarda, 2004). El May et al (2009) has proved that static magnetic field (SMF) exposure could alter cell growth, viability, and gene expression in some bacteria.…”
mentioning
confidence: 99%
“…As it is more difficult to evaluate the effect of low-intensity magnetic fields because it may interfere with the earth's magnetic field and because results are often conflicting, we selected a high induction (200 mT) field. The static magnetic field exposure (200 mT) induced a stress status in S. Hadar (El May et al 2009). Furthermore, Pickering et al (2003) showed that the Staphylococcus epidermidis biofilms had greatly increased susceptibility to gentamicin.…”
Section: Discussionmentioning
confidence: 99%
“…Among these have been the effects on cell growth, proliferation and cell viability (Raylman et al 1996;Potenza et al 2004b;Ji et al 2009;Obermeier et al 2009), cell morphotype (Cellini et al 2008), increased calcium influx Amara et al 2004), altered DNA in terms of point mutations (Potenza et al 2004a), inhibition of nocturnal levels of melatonin (Brendel et al 2000), protein synthesis (Goodman et al 1993), transport of ions by cell membranes (D'Inzeo et al 1993) and gene transcription (Phillips et al 1992). In terms of electromagnetic field action in bacteria, several papers have reported alterations on growth, DNA molecules and gene expression Potenza et al 2004b;El May et al 2009). Escherichia coli cells exposed to an extremely low frequency magnetic field (0.1 T) for 6.5 h exhibited changes in viability compared to unexposed cells, which had a viability 100 times higher than the control (Justo et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there was a decrease in the viability of Helicobacter pylori after exposure to ELF-EMF ( Di Campli et al , 2010 ), whereas Salmonella enterica subsp. enterica serovar Hadar showed overexpression of the genes rpoA , katN , and dnaK ( El May et al , 2009 ). To date, few studies have used omics techniques to evaluate the gene expression profile of organisms exposed to electromagnetic fields.…”
mentioning
confidence: 99%